Parental attachment in childhood and quality of the romantic relationships of young adults: the mediating effect of adult attachment - Martínez-Álvarez, Jose L.; Fuertes-Martín, Antonio; Orgaz-Baz, Begoña; Vicario-Molina, Isabel; González-Ortega, Eva (Anales de Psicología / Annals of Psychology, 2013)
This paper has two main aims: firstly, to explore the relationship between parental attachment in childhood and perceived quality of romantic relationships in youth; secondly, to assess the possible mediating effect of adult attachment in the romantic relationship. A total of 133 heterosexual couples (ages 17-25) voluntarily participated in the study. An online questionnaire was applied to both partners to evaluate the quality of the relationships with the father and the mother in childhood, the attachment to partner (Anxiety-Avoidance), and the perceived quality of the romantic relationship. The results showed significant positive associations between parental attachment in childhood and the quality of the romantic relationship, which were mediated by the adult attachment to partner. Furthermore, negative associations were detected between anxiety and avoidance of each partner and their own relational experience (and the other’s relational experience, in some cases). These results are discussed in terms of attachment theory and their significance to the quality of the romantic relationship.